Laser-assisted photoionization: Streaking, sideband, and pulse-train cases - Della Picca, Renata (2020)
We present a theoretical study of atomic laser-assisted photoionization emission. We consider an atom driven by a linearly polarized extreme ultraviolet laser in two scenarios: (i) a single attosecond pulse (in both the streaking and the sideband regimes) and (ii) an attosecond pulse train. The process takes place assisted by a linearly polarized infrared laser field. In all these cases the energy- and angle-resolved photoelectron spectrum (PES) is determined by a leading contribution, related to the intracycle factor [Gramajo et al., J. Phys. B 51, 055603 (2018)], complemented by other ones, derived from the periodicity and symmetry properties of the dipole transition matrix with respect to the infrared field. Each of these terms imprint particular features in the PES that can be straightforwardly understood in terms of generalized energy conservation laws. We investigate in detail these PES structures, in particular, for the case of argon initially in the 3s quantum state. Our theoretical scheme, based on the strong-field approximation, can be applied, however, to other atomic species and field configurations as well.